Perancangan Sistem Informasi Dokumen Ekspor Berbasis Desktop Netbeans Pada PT. Angkasa Raya Djambi - Gultom, Brestina; Anderson, Ryan; Amri, Imti Tsalil (LPPM Universitas Dinamika Bangsa, 2024)
Most business fields, offices and government agencies require computer technology as a tool to solve work problems such as documentation problems where every documentation must be recorded as an archive. Making export documents of PT. Angkasa Raya Djambi, which is still using the Microsoft Word and Excel application program, where there are still some problems, namely every export cargo activity has been carried out, preparation of document creation and archiving is still required to create new files which causes the file storage space to increase over time. Sometimes there are also difficulty in the process of finding data files for report generation where you have to open the files again one by one or reopen the export document files directly for the input process into excel. This research produces an information system for making export documents based on the Netbeans desktop. This information system is the right step in solving problems that exist in PT. Angkasa Raya Djambi in the need to manage export documents more easily, quickly and automatically